Endocytic structures and synaptic vesicle recycling at a central synapse in awake rats - Körber, Christoph; Horstmann, Heinz; Kuner, Thomas (Traffic, 2012)
The synaptic vesicle (SV) cycle has been studied extensively in cultured cells and slice preparations, but not much is known about the roles and relative contributions of endocytic pathways and mechanisms of SV recycling in vivo, under physiological patterns of activity. We employed horseradish peroxidase (HRP) as an in vivo marker of endocytosis at the calyx of Held synapse in the awake rat. Ex vivo serial section scanning electron microscopy and 3D reconstructions revealed two categories of labelled structures: HRP-filled SVs and large cisternal endosomes. Inhibition of adaptor protein complexes 1 and 3 (AP-1, AP-3) by in vivo application of Brefeldin A (BFA) disrupted endosomal SV budding while SV recycling via clathrin-mediated endocytosis (CME) remained unaffected. In conclusion, our study establishes cisternal endosomes as an intermediate of the SV cycle and reveals CME and endosomal budding as the predominant mechanisms of SV recycling in a tonically active central synapse in vivo.